Онтоморфогенез вічнозелених видів роду Rhododendron L. ex situ - Shumyk, M.I.; Kliuienko, O.V.; Korkulenko, O.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to study the peculiarities of formation of morphological structures and mechanisms of adaptation to new conditions at the initial stages of ontomorphogenesis of evergreen species of the genus Rhododendron L. introduced in the M.M. Gryshko National Botanical Garden of the NAS of Ukraine (NBG); to identify critical periods and limiting factors at different stages of development of their seedlings under the conditions of primary culture. Material and methods. The object of the study is the evergreen species of the genus Rhododendron introduced in NBG (R. catawbiense Michx., R. dauricum L., R. degronianum Carrié). The study was carried out in 2005–2017 at the greenhouse conditions and in areas of department of landscape construction of NBG according to commonly accepted methods. We used recommendations R.Ya. Kondratovych (1981), A.U. Zarubenko (2006), I.M. Koksheyeva (2009), M.S. Alexandrova (1986), L.V. Vegera (2006) and others. Results. At seed reproduction of studied evergreen species of rhododendrons under ex situ conditions (in case optimal illumination and humidity temperature regime, soil acidity are provided, any critical periods are not revealed at the initial stages of ontomorphogenesis. The seeds of the species studied had high germination (65–90 %). In the conditions of primary culture in NBG seedlings of studied species are able to withstand the conditions of open ground in the winter period starting from the immature growing state. The seedlings reach a young generative state at 3–5 (R. dauricum) and 6–7 (R. catawbiense, R. degronianum) year. All studied species produce germinating seeds. Conclusions. While ensuring the necessary conditions the investigated species of evergreen rhododendrons successfully adapt, pass all the initial stages ontomorphogenesis. Immature, virginal and young generative individuals satisfactorily tolerate conditions of open ground, showing sufficient frost resistance. In the conditions of the primary culture in NBG seedlings are blooming, fruiting, give viable seeds. Studied species are promising for use in landscaping, for instance in the city of Kyiv.